EVALUASI PELAKSANAAN REVEGETASI PADA LAHAN PASCATAMBANG BATUBARA (STUDI KASUS DI PT. X DI KABUPATEN TANAH BUMBU PROVINSI KALIMANTAN SELATAN) - Fathurrahman, Fathurrahman; Kissinger, Kissinger; Achmad, Basir; Abidin, Zainal (Universitas Lambung Mangkurat, 2023)
Coal mining company in PT. X, in Tanah Bumbu District, South Kalimantan Province, uses the open-pit mining method, causing the initial vegetation loss of an area. PT. X has rehabilitated areas affected by mining by reclamation and revegetation to comply with government regulations. The types of vegetation that grew in the post-mining land revegetation area in the planting years 2012, 2014 and 2016 were acacia (Acacia mangium WILLD), trambesi (Samanea saman), sea sengon (Paraserianthes falcataria), and woody and fruit plants such as mahogany (Swietenia macrophylla), agarwood (Aquilaria moluccensis), meranti (Shorea Spp.), sungkai (Peronema canescens), rubber (Hevea brasiliensis), durian (Durio zibethinus), jackfruit (Artocarpus heterophylla), cashew (Anacardium occidentale), mango (Mengifera indica) and galam (Melaleuca cajuputi). Land characteristics have a steep slope of 35° in 2012 and range from 5°-20° in 2014 and 2016 The drainage system for planting years 2012, 2014 and 2016 looks good no erosion strains, planting years 2014 sites are flooded. The results of soil analysis are pH 4.48 - 4.97; the value of C-organic compounds 0.20% (very low) - 1.33% (medium); P2O5 1.89 mg/100g-1 (very low) - 40.10 mg/100g-1 (high); K2O with values of 8.57 mg/100g-1 (low) - 15.50 mg/100g-1 (medium), 0.20 me/100g-1 (very low) – 19.59 me/100g-1 (low); Mg-exchange at a value of 0.10 me/100g-1 (very low) - 0.20 me/100g-1 (low); Na-exchange of 0.05 me/100g-1 - 0.10 me/100g-1 is low; K-exchange with a value of 0.03 me/100g-1 - 0.05 me/100g-1 is very low, CEC 27.85 me/100g-1 - 52.48 me/100g-1 is low, saturation 0.95% (very low) - 41.56 (high). Based on the success rate of reclamation with revegetation parameters according to the Regulation of the Minister of Forestry No.P.60/Menhut-II/2009, it can be concluded that the success of revegetation obtained for the overall value with an overall value of 24 out of the target value of 50 with a percentage of plant growth of 27%, then the success value of revegetation is categorized as low.